Microsoft windows server 2008 : - Matthews, Marty (McGraw hill, 2008)
Microsoft Windows Server 2008: A Beginner's Guide shows you how to set up the server, migrate from earlier versions, and handle networking, administration, storage, and security. You'll also get details on the new Web tools and management utilities available in Windows Server 2008.